A Comprehensive Analysis of Ionospheric Anomalies before the Mw7·1 Van Earthquake on 23 October 2011. (25th October 2018) - Şentürk, Erman; Livaoğlu, Hamdullah; Çepni, Murat Selim
Abstract : In this study, possible ionospheric precursors of the Mw 7·1 Van earthquake are investigated with temporal, spatial and spectral analyses. For this purpose, Global Navigation Satellite System (GNSS) data of 11 International GNSS Service (IGS) stations and 17 Turkish National Permanent Real-Time Kinematic (RTK) Network (TNPGN-Active) stations were utilised. In addition, Global Ionosphere Map (GIM) data produced by the Center for Orbit Determination in Europe (CODE) was used to obtain GIM-vertical Total Electron Content (vTEC) values for the epicentre. The results of the temporal and spectral analysis indicate an increase (2–8 Total Electron Content Units (TECU)) before the Van earthquake occurred on 9 October, 15–16 October and 21–23 October within 15 days, 8–9 days and 1–3 days prior to the earthquake. The Cross-Wavelet Transform (CWT) method was used to examine the presence of correlation between noticeable variations and space-weather. It is deduced from the CWT analysis that the anomalies should originate from either solar effects or the Van earthquake due to coupling between the F10·7 solar activity index and TEC variations on the anomaly days. The results demonstrate that interdisciplinary approaches and various methods including frequency domain could be used to determine the presence of an earthquake-related anomaly in the ionosphere accurately.